ANALISIS ARUS KAS PADA UD. MARGA DINATA CELL DI SAMARINDA - Mardiana, Rinus Baene H. Eddy Soegiarto K (EKONOMIA, 2015)
This study aims to determine the operational activities, funding, investment cash flow generated from operating activities and sales at UD. Marga Dinata Cell Samarinda. Accurate financial information in decision-making is the cash flow statement. Cash flows in a company, it is useful to users of the financial statements as a basis for assessing the ability of the company to achieve cash and cash equivalents in the assessment of the company needs to put on cash flow. Cash is the most useful concept funds, because the decision of the investors, creditors and other parties focused on the assessment of future cash flows. The company will utilize idle cash by investing in a very short ranges investment likiud. Financial report is basically the result of the accounting process that can be used as a tool for communication between financial data or activities of a company with the parties concerned with the data or activities of the company. Users of financial statements includes current investors and potential investors, employees, lenders, suppliers and other business creditors, customers, governments and institutions and will use the information society in which the financial statements are different. The foregoing description can be expressed as the following hypothesis: